The faith of scientists in their own words - Frankenberry, Nancy, 1947-; NetLibrary, Inc. (Princeton : Princeton University Press, 2008)
The Faith of Scientists is an anthology of writings by twenty-one legendary scientists, from the dawn of the Scientific Revolution to the frontiers of science today, about their faith, their views about God, and the place religion holds--or doesn't--in their lives in light of their commitment to science. --From publisher description.
Founders of modern science. Galileo Galilei (1564-1642) -- Johannes Kepler (1571-1630) -- Francis Bacon (1561-1626) -- Blaise Pascal (1623-1662) -- Isaac Newton (1643-1727) -- Charles Darwin (1809-1882) -- Albert Einstein (1879-1955) -- Alfred North Whithead (1861-1947) -- Scientists of our time. Rachel Carson (1907-1964) -- Carl Sagan (1934-1996) -- Stephen Jay Gould (1941-2002) -- Richard Dawkins (1941-) -- Jane Goodall (1934-) -- Steven Weinberg (1933-) -- John Polkinghorne (1930-) -- Freeman Dyson (1923-) -- Stephen Hawking (1942-) -- Paul Davies (1946-) -- Edward O. Wilson (1929-) -- Stuart A. Kauffman (1939-) -- Ursula Goodenough (1944-).
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Religion and science; Scientists -- Religious life; Electronic books